Significant pain reduction and improved functional outcome after surgery for displaced midshaft clavicular fractures. Issue 1 (December 2015) - Eden, Lars; Ziegler, Dirk; Gilbert, Fabian; Fehske, Kai; Fenwick, Annabel; Meffert, Rainer
Abstract Purpose Displaced midshaft clavicular fractures can be treated conservatively as well as operatively by titan elastic nail (TEN) or plate fixation. This survey was performed to evaluate the clinical results of each treatment method and elaborate advantages or possible complications of each modality. Methods Between 2008 and 2013, 102 patients were prospectively included in our study—37 patients for conservative treatment with a rucksack bandage for 4 to 6 weeks, 41 patients for plate osteosynthesis, and 24 for intramedullary stabilization with TEN. Disabilities of the Arm, Shoulder and Hand (DASH), Constant Murley Score (CMS), and visual analog scale (VAS) for pain and function as well as time of invalidity were recorded over a 1-year period. Results The clinical data collected reveals that all three different therapies lead to good or excellent clinical results after 1 year. However, one can observe advantages of operative treatment in comparison to conservative therapy in some characteristics. Conclusion Our data shows that there are several indications where operative treatment has advantages compared to conservative treatment. In special fracture types (Robinson 2B1), TEN gives the best results. Plate fixation is extraordinarily sufficient in pain reduction within the first 5 weeks and indicated in more-part fractures (Robinson 2B2). Nevertheless, conservative treatment is always a good and promising way to treat clavicular fractures, so that individual indications and thorough patient informative talks are inevitable.